M-Mode Ultrasound Reveals Earlier Gluteus Minimus Activity in Individuals With Chronic Hip Pain During a Step-down Task - Dieterich, A.; Deshon, L.; Strauss, Geoff; McKay, J.; Pickard, Christine (2016)
Study Design: Controlled laboratory study. Background: The hip abductor muscles are important hip joint stabilizers. Hip joint pain may alter muscle recruitment. Motion-mode (M-mode) ultrasound enables noninvasive measurements of the onset of deep and superficial muscle motion, which is associated with activation onset. Objectives: To compare (1) the onset of superficial and deep gluteus medius and gluteus minimus muscle motion relative to the instant of peak ground reaction force and (2) the level of swing-phase muscle motion during step-down between subjects with chronic hip pain and controls using M-mode ultrasound. Methods Thirty-five subjects with anterior, nontraumatic hip pain for more than 6 months (mean ± SD age, 54 ± 9 years) and 35 controls (age, 57 ± 7 years) were scanned on the lateral hip of the leading leg during frontal step-down onto a force platform using M-mode ultrasound. Computerized motion detection with the Teager-Kaiser energy operator was applied on the gluteus minimus and the deep and superficial gluteus medius to determine the time lag between muscle motion onset and instant of peak ground reaction force and the level of gluteus minimus motion during the swing phase. Time lags and motion levels were averaged per subject, and t tests were used to determine between-group differences. Results In participants with hip pain, gluteus minimus motion onset was 103 milliseconds earlier (P = .002) and superficial gluteus medius motion was 70 milliseconds earlier (P = .047) than those in healthy control participants. The level of gluteus minimus swing-phase motion was higher with pain (P = .006). Conclusion Increased gluteus minimus motion during the swing phase and earlier gluteus minimus and superficial gluteus medius motion in individuals with hip pain suggest an overall increase of muscle activity, possibly a protective behavior.These results have potential implications for understanding transport and reduction of seawater-derived sulfate in submarine hydrothermal systems. The formation of an immiscible sulfate-rich liquid phase can favor the circulation of sulfate within mid-ocean ridge basalt because the sulfate-rich liquid density is higher than that of the coexisting fluid. The reduction of sulfate could also be accelerated because sulfate is locally concentrated and strong Zn2+-SO4 2- association increases the reactivity of sulfate.